Analysis of Implementation Plan of Science Learning and the Factors of ITS Implementation in MTs and MA Al Khoiriyyah Semarang - Sabdhosih, Has; Isnaeni, Wiwi; Nugrahaningsih, Nugrahaningsih (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
The learning process requires a plan, so that what is done can run and produce something as expected. With such a plan, the process to be carried out over a long period of time has a clear direction, predictable results, predictable resources required, and can be used to determine the requirements of students in following the learning process in the school. The purpose of this study is to analyze the conformity and implementation of RPP, as well as supporting factors and inhibiting the implementation of science learning in MTs and MA Al Khoiriyyah Semarang. The method used in this research is qualitative research with case study method. This research takes place in Madrasah Tsanawiyah (MTs) and Madrasah Aliyah Al Khoiriyyah Semarang. Sources of data in this study are teachers of science lessons in MTs Al Khoiriyyah and physics, chemistry, biology teacher at MA Al Khoiriyyah. Data collection techniques used consisted of observation, interview, documentation and student response questionnaire. The results showed that the quality of RPP in MTs and MA Alkhoiriyyah was in accordance with Permendikbud number 22 of 2016 with very good criteria. The implementation of science learning in MTs and MA Alkhoiriyyah has been in accordance with Permendikbud number 22 of 2016 with good category. Factors supporting the implementation of RPP in learning is the source of learning and supporting facilities such as libraries, laptops, LCDs, and the internet. While the inhibiting factors are time constraints, students are less active, and the teacher's understanding is still lacking in combining the methods, models, and learning strategies with a scientific approach. Implementation of science learning activities in MTs and MA Al Khoiriyyah received a good response from learners.